5G for Business - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (International Journal of Human Computing Studies, 2023)
5G stands for fifth generation of cellular networking, surpassing 4G LTE It is expected to change the way we live and work. 5G technology is developing rapidly to enable the next generation of wireless communications and paving the way for more than just super-fast data transfer. 5G wireless technology will usher in an era of gigabit speeds for everyone, reducing latency to customers and organizations. The advent of 5G technology will not only transform our devices but will also significantly change the way businesses operate, communicate, connect, and share data. 5G is expected to be a game-changer to the business world. This article deals with how 5G technology works and how it is applied in business.